Tinular Tutur : Audio Drama Media Counter Hegemony Ruler of The New Order (Analysis of Critical Discourse) - Purwanto Lephen (Dance and Theatre Review, 2021)
The heyday of the 1980-1990 audio drama created by the Sanggar Cerita and the Teater Sanggar Prativi, Jakarta, Indonesia, was an industrial production of drama initiatives synergize between drama creators, pharmaceutical companies and herbal medicine as sponsors, and private radio companies that broadcast them. The productivity of audio drama works in the New Order era reached dozens of titles; some audio drama works produced up to 720 series or 24 episodes for two years broadcast. The audio drama Tutur Tinular by S. Tidjab uses history in Java (Singasari, Kediri, Majapahit) as a source of creation. Critical Discourse Analysis used (Norman Fairclough) is used to reveal texts, practices of discourse. Between social practices were resulting in the finding that in the audio drama, Tutur Tinular contains the behaviour of kings (rulers), royal authorities (patih, warlords), warriors (good people), criminals (bad people), and persecuted people. In the power New Order era, audio drama, which was considered an entertainment media and educational history of nationalism, was a media of resistance of the New Order military rulers.  It contained the rulers' behaviour and soldiers who oppressed their people, but it never received a reprimand and a ban on the authorities until the regime subsided.Keywords: drama audio, counter-hegemony, critical discourse